Applied Regression Modelling to Recommend Microfinance Development Policies - Huy, Nguyen Quoc; Nga, Lu Phi; Tam, Phan Thanh (Bright Publisher, 2023)
Microfinance plays an essential role in the socio-economic development of each country through support for poverty reduction. In Vietnam, hunger eradication and poverty reduction under the National Target Program have received attention and implementation in recent years. However, during 2020-2021, Vietnam had several difficulties and hurdles for microfinance organizations, exacerbated by the Covid-19 outbreak, which was hurting the country and all sectors of social life. Microfinance is an excellent instrument for long-term poverty reduction since it teaches the poor how to do business and save and provides essential information. However, microfinance has not yet reached its full potential in our nation. One of the suggested reasons is the legal framework impediment. Thus, the research examines the State's policies for microfinance operations using a survey of 260 staffs related to microfinance activities from 30 microfinance organizations and 30 commercial banks in Vietnam, with data processed using SPSS 20.0. Finally, the study's value suggests ideas for removing barriers to continued microfinance activity development in Vietnam.